The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The Potato Crop 2020
DOI: 10.1007/978-3-030-28683-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Viral Diseases in Potato

Abstract: Viruses are among the most significant biotic constraints in potato production. In the century since the discovery of the first potato viruses we have learned more and more about these pathogens, and this has accelerated over the last decade with the advent of high-throughput sequencing in the study of plant virology. Most reviews of potato viruses have focused on temperate potato production systems of Europe and North America. However, potato production is rapidly expanding in tropical and subtropical agro-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 104 publications
1
102
0
5
Order By: Relevance
“…The story in our review started in 1931, with PVY, one of the first two described viruses of potato, but now, nine decades later, at least 49 more viruses of potato have been recorded [163]. The group of viruses, of which PVY is the type, is now represented in GenBank by genomic sequences of more than 150 different potyviruses and a third as many other potyvirids.…”
Section: Discussionmentioning
confidence: 99%
“…The story in our review started in 1931, with PVY, one of the first two described viruses of potato, but now, nine decades later, at least 49 more viruses of potato have been recorded [163]. The group of viruses, of which PVY is the type, is now represented in GenBank by genomic sequences of more than 150 different potyviruses and a third as many other potyvirids.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that a single mutation can shift the outcome [14]. On the other hand, studies of PVY strains showed an exceptional diversification via nucleotide mutation and genome recombination resulting in new strains and isolates with different degrees of pathogenicity [1,[15][16][17]. Often, outcomes of the interaction in the same potato genotype are different, depending on PVY strain, as was shown for PVY N and PVY NTN in cvs.…”
Section: Introductionmentioning
confidence: 99%
“…Potato virus Y (PVY) is the most economically important virus affecting potato production worldwide [1]. It severely affects potato production in terms of crop yield and quality, which, in the case of secondary infections, can reach yield reductions up to 85% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Its production is of particular economic importance, with potato ranked fourth globally in food crops behind maize, wheat and rice (Djebli et al, 2020). In the last decades, global production increased at a much higher rate with regard to other staple crops (Kreuze et al, 2020). In Canada, a 23% increase in potato production was observed from 2008 to 2018 (FAO, 2018).…”
Section: Introductionmentioning
confidence: 99%